Diet and exercise interventions reduce serum asprosin and the corresponding hypothalamic– pituitary–gonad-axis dysfunction in obese men - Yao, Tingting; Song, Chenglin; Yu, Yajie; Cheng, Yang; Lu, Hongyan; Li, Jing; Yang, Yang; Tang, Donghui; Yi, Xuejie (Frontiers in Physiology, 2022)
Background: Asprosin (ASP) is a recently discovered adipocyte factor that participates in glucose metabolism and inflammatory reactions. Recent findings suggest that it may be involved in the regulation of sex hormone secretion in the hypothalamic-pituitary-gonad (HPG) axis, but no studies have been reported in related populations. The purpose of this study was to evaluate the changes in serum ASP levels in healthy men and obese men, as well as before and after exercise weight loss, and to investigate male hypogonadism, insulin resistance, inflammatory response, and relationships induced by ASP and obesity. Methods: Thirty-eight young male volunteers were recruited and divided into a normal group (n=20) and an obese group (n=18) according to their body mass index. Fourteen of the obese men underwent a 14-week exercise and diet intervention (first 8 weeks of aerobic exercise at 60%–70% HRmax for 30–50 min/ four days a week). Beginning at week 9, the intensity was increased to 75% HRmax. Participants in the obese groups maintained a calorie-restricted diet throughout the study period. Results: Serum ASP levels in the obese group were significantly higher than those in the normal group, and serum gonadotropin-releasing hormone (GnRh), luteinizing hormone (LH), and testosterone (T) levels were decreased. After 14 weeks of exercise and diet intervention, serum ASP decreased significantly, the levels of body weight, lean body weight, body fat rate, fasting insulin (FINS), homeostatic model assessment for insulin resistance, TNF-α, IL-6, and IL-1β decreased significantly, and the serum GnRH, LH, and T levels increased significantly. ASP was positively correlated with body weight, body fat percentage, FINS, tumor necrosis factor (TNF)-α, interleukin (IL)-6, and IL-1β and negatively correlated with relative lean body weight and serum LH and T levels. Conclusion: The serum ASP levels were increased in obese men compared with those of normal weight individuals, resulting in a chronic inflammatory reaction, high serum insulin, and HPG axis injury. Fourteen weeks of exercise and diet intervention effectively alleviated this phenomenon. It has been speculated that ASP might regulate male reproductive function by regulating the inflammatory response and insulin sensitivity.